A 3-D hydraulic fracture propagation model applied for shale gas reservoirs with multiple bedding planes. (1st April 2020) - Xie, Jun; Tang, Jizhou; Yong, Rui; Fan, Yu; Zuo, Lihua; Chen, Xing; Li, Yuwei
Highlights: A full three-dimensional fracture propagation model was proposed. Distribution of shear displacement discontinuities along the bedding planes was analyzed. Effect of number of bedding planes on fracture height growth was investigated. Type curve of leak-off ratio and fracture half-height was introduced for detecting BP number. The 'furcation' in ξ - η plot was used to verdict the fracture crossing of a new BP. Abstract: Rock layering, a critical factor in determining fracture height growth, is pervasive in Longmaxi shale formation in the southwest of China. This formation has characteristics of large burial depth, low porosity and multiple bedding layers that hamper reaching the target fracture height even after increasing the pumping rate and treatment size. Hence, it becomes much significant to develop a fracture propagation model considering the effect of bedding layers on fracture height growth. This paper introduces a coupled 3-D hydraulic fracture propagation model and investigates the influence of shear displacement discontinuities along bedding planes on fracture height growth. Our model addresses rock deformation and fluid flow. Rock deformation is governed by a fully three-dimensional displacement discontinuity method (3D DDM). The fluid flow model employs a finite difference method (FDM) being able to capture fluid movement along vertical fractures and bedding planes. Additionally, a propagation criteria determines whether the fracture would penetrate bedding planes. In this paper, we selected two different fracture geometries and analyzed profiles of fracture width, pressure and two types of shear displacement discontinuities. From numerical investigations, we found that the maximum width can be obtained at the junction after the vertical fracture penetrated the bedding planes as a result of the decrement of the compressive stress acting on the bedding planes. As the fracture penetrates the bedding planes, a certain amount of fluid would leak into the planes, which leads to fracture height containment. Moreover, the slope utilized for characterizing the correlation between leak-off volume and fracture height, is regarded as a tool to identify the number of BPs that fracture penetrates through. This paper illustrates the potential application of our 3-D fracture propagation model for Longmaxi shale formation with multiple bedding layers. Shear displacements along bedding planes are regarded as a primary mechanism of fracture height containment.